2019
DOI: 10.3390/pathogens8040259
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Scotophilus Bat Coronavirus-512 and Severe Acute Respiratory Syndrome Coronavirus in Human and Multiple Animal Cells

Abstract: Bats are natural reservoirs of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV). Scotophilus bat CoV-512 demonstrates potential for cross-species transmission because its viral RNA and specific antibodies have been detected in three bat species of Taiwan. Understanding the cell tropism of Scotophilus bat CoV-512 is the first step for studying the mechanism of cross-species transmission. In this study, a lentivirus-based pseudovirus was produced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The six Pedacovirus-like BtCoV sequences described in this study are phylogenetically related to both PEDV and Scotophilus bat coronavirus 512. PEDV has been shown to bind to aminopeptidase-N (APN), but not necessarily as the only receptor, while Scotophilus bat coronavirus 512 is able to infect a wide range of cultured cell types without the use of APN [71]. To our knowledge, no cell receptors have been described for the Alphacoronavirus subgenera Nyctacovirus and Myotacovirus, but for other subgenera in this genus, APN, angiotensin-converting enzyme 2 (ACE2), N-glycolylneuraminic acid (Neu5Gc), and N-acetylneuraminic acid (Neu5Ac) are known receptors [72].…”
Section: Discussionmentioning
confidence: 99%
“…The six Pedacovirus-like BtCoV sequences described in this study are phylogenetically related to both PEDV and Scotophilus bat coronavirus 512. PEDV has been shown to bind to aminopeptidase-N (APN), but not necessarily as the only receptor, while Scotophilus bat coronavirus 512 is able to infect a wide range of cultured cell types without the use of APN [71]. To our knowledge, no cell receptors have been described for the Alphacoronavirus subgenera Nyctacovirus and Myotacovirus, but for other subgenera in this genus, APN, angiotensin-converting enzyme 2 (ACE2), N-glycolylneuraminic acid (Neu5Gc), and N-acetylneuraminic acid (Neu5Ac) are known receptors [72].…”
Section: Discussionmentioning
confidence: 99%
“…Here we briefly review these viruses. In terms of animal infectious coronaviruses, alphacoronaviruses include transmissible gastroenteritis virus [38] , porcine-respiratory coronavirus [39] and porcine-epidemic diarrhea virus [40] infecting pigs; feline-CoV affecting cats [41] ; bat coronaviruses such as Scotophilus bat CoV-512, Rhinolophus bat CoV-HKU2, Miniopterus bat CoV 1A/B and CoV-HKU8 infecting various species of bats [42] , [43] , [44] , [45] .…”
Section: Animal and Human Infectious Coronavirusesmentioning
confidence: 99%
“…It has been shown that angiotensin-converting enzyme 2 (ACE2) receptors present on host cells are used by the SARS-CoV-2 for viral entry 25 . ACE2 receptors have been shown to be present on MDCK cells 23 26 . This probably indicates that post-adsorption mechanisms and/or cell machinery of the MDCK cell line do not allow replication of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%